FACTORS INFLUENCING TEACHERS’ INTENTIONS TO USE REALISTIC MATHEMATICS EDUCATION IN VIETNAM: AN EXTENSION OF THE THEORY OF PLANNED BEHAVIOR - Do, Thi-Trinh; Hoang, Kien Cong; Do, Tung; Trinh, Thao Phuong Thi; Nguyen, Danh Nam; Tran, Trung; Le, Trung Thien Bao Thai; Nguyen, Thanh Chi; Nguyen, Tien-Trung (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2021)
Although Realistic Mathematics Education (RME) has become familiar to many mathematics teachers, we still have little understanding of the extent to which mathematics teachers are willing to employ RME rather than traditional teaching approaches. Based on the theory of planned behavior, in conjunction with some other factors, including facilitating conditions and perceived autonomy, this study investigated a model explaining the continued intention of mathematics teachers to use Realistic Mathematics Education. A structural equation model was used to access data from an online survey involving 500 secondary school mathematics teachers in Vietnam. The results revealed that while attitude, perceived behavioral control and perceived autonomy have positive significant impacts on intention to use RME, it appears that subjective norms and facilitating conditions do not. These findings are of significance to stakeholders, including policymakers, school managers, and mathematics teachers.